Hypoxia and Time of Useful Consciousness in Hypobaric Chamber at 25,000 feet in Aircrew at dr. Saryanto Health Institute of Aeronautics and Space - Putri, Nabila Tita Azalia; Savitri, Pritha Maya; Kristanti, Melly; Irawan, Agneta Irmarahayu (Universitas Airlangga, 2024)
Introduction: Hypoxia is a condition characterized by insufficient oxygen supply to tissues which causes body tissues to fail to get adequate oxygen supply. Hypobaric hypoxia is generally recognized as the most serious physiological hazard during high-altitude flight. This puts active crew members at risk for hypoxia and so they rely on effective performance time (EPT) or time useful consciousness (TUC) to take appropriate corrective and protective actions when hypoxia occurs. This study aimed to describe TUC scores and hypoxia symptoms experienced by active flight crew at dr. Saryanto Health Institute of Aeronautics and Space in 2021. Methods: A descriptive research design using medical record data from 99 flight crew with simple random sampling. The variables in this study consisted of hypoxia symptoms and TUC scores. This study uses univariate analysis to see the frequency distribution of the variables of hypoxia symptoms and TUC score. Results: The results showed that 18.2% experienced cognitive symptoms, 4% experienced psychomotor symptoms, 16.2% experienced visual symptoms, 3% experienced psychological symptoms, 54.5% experienced non-spesific symptoms, and 37.4% did not feel any symptoms. Most of the flight crew (68.7%) had sufficient EPT/TUC scores (3-4 minutes). Conclusion: Active flight crews feel symptoms of hypoxia and have sufficient TUC scores.